Images, ’Superstition’, and Popular Piety in Post-Reformation Sweden - Zachrisson, Terese (Mirator, 2018)
Though the Lutheran church in Sweden never sought to ban pre-reformation images from church space, these objects remained controversial and provoked a variety of different responses from clergy and parishioners throughout the early modern era. Some images continued to be venerated as vessels of supernatural power, albeit in new contexts. Seventeenth-century vicars often tolerated or even condoned popular practices that their superiors deemed superstitious or idolatrous. Among the clerical élite images were not always considered to be adiaphora — as was stated in the Church Ordinance — but some images were believed to be harmful in themselves in provoking unwanted responses among parishioners.